2019
DOI: 10.1177/1075547019847484
|View full text |Cite
|
Sign up to set email alerts
|

Science, Values, and Science Communication: Competencies for Pushing Beyond the Deficit Model

Abstract: The deficit (knowledge transmission) model of science communication is widespread and resistant to change, highlighting the limited influence of science communication research on practice. We argue that scholar-practitioner partnerships are key to operationalizing science communication scholarship. To demonstrate, we present a transformative product of one such partnership: a set of ethics and values competencies to foster effective communication with diverse audiences about scientific research and its implica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
49
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 17 publications
1
49
0
3
Order By: Relevance
“…Without such reflexivity, experts may consider their conclusions about risk are neutral, unbiased and free from any social and cultural context, with serious negative consequences for participatory communication [Metcalfe, 2019;Turner, 2001]. Scientific research is still firmly embedded in a positivist approach to knowledge [Seethaler et al, 2019], despite decades of research demonstrating the value of other ways of knowing [Douglas, 1986;Freudenburg, 1988;Slovic, 1999;Wynne, 1989]. The continuing default of using the deficit model of science communication corroborates this [Mogendorff, te Molder, Gremmen et al, 2012;Raps, 2016;Seethaler et al, 2019].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Without such reflexivity, experts may consider their conclusions about risk are neutral, unbiased and free from any social and cultural context, with serious negative consequences for participatory communication [Metcalfe, 2019;Turner, 2001]. Scientific research is still firmly embedded in a positivist approach to knowledge [Seethaler et al, 2019], despite decades of research demonstrating the value of other ways of knowing [Douglas, 1986;Freudenburg, 1988;Slovic, 1999;Wynne, 1989]. The continuing default of using the deficit model of science communication corroborates this [Mogendorff, te Molder, Gremmen et al, 2012;Raps, 2016;Seethaler et al, 2019].…”
Section: Discussionmentioning
confidence: 99%
“…Scientific research is still firmly embedded in a positivist approach to knowledge [Seethaler et al, 2019], despite decades of research demonstrating the value of other ways of knowing [Douglas, 1986;Freudenburg, 1988;Slovic, 1999;Wynne, 1989]. The continuing default of using the deficit model of science communication corroborates this [Mogendorff, te Molder, Gremmen et al, 2012;Raps, 2016;Seethaler et al, 2019]. Appropriate consideration needs to be given to increasing the transparency of assumptions about neutrality in scientific research and the impact of those assumptions on risk communication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the development of the project, it was found that the complex nature of on farm biosecurity surveillance, means they are not responsive to top-down approaches of communication and management [Maru et al, 2017]. A common top-down approach is the deficit model of science communication that sees provision of more information or regulation as sufficient for problem solving [Seethaler et al, 2019]. Instead, the AIS approach allows participants to flip the traditional top-down deficit model approach to disease surveillance.…”
Section: Discussionmentioning
confidence: 99%